2020
DOI: 10.1101/2020.03.03.975789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early maturational emergence of adult-like emotional reactivity and anxiety after brief exposure to an obesogenic diet

Abstract: Background: Emerging evidence demonstrates that diet-induced obesity disrupts corticolimbic circuits underlying emotional regulation. Studies directed at understanding how obesity alters brain and behavior are easily confounded by a myriad of complications related to obesity. This study investigated the early neurobiological stress response triggered by an obesogenic diet. Furthermore, this study directly determined the combined impact of a short-term obesogenic diet and adolescence on critical behavioral and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
2
4
0
Order By: Relevance
“…We have modeled this relationship by measuring stress reactivity to traumatic stress in a rat model of diet-induced obesity (DIO). Consistent with studies in obese adolescents, we reported that adolescent diet-induced obesity (DIO) in rats: 1) reduces hippocampal volume [12], 2) impairs the maturation of the corticolimbic fear circuits [13], 3) enhances behavioral vulnerabilities to psychosocial stress [12][13][14], and 4) results in profound fear extinction learning deficits [13,14], even in the absence of an obesogenic phenotype [15].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…We have modeled this relationship by measuring stress reactivity to traumatic stress in a rat model of diet-induced obesity (DIO). Consistent with studies in obese adolescents, we reported that adolescent diet-induced obesity (DIO) in rats: 1) reduces hippocampal volume [12], 2) impairs the maturation of the corticolimbic fear circuits [13], 3) enhances behavioral vulnerabilities to psychosocial stress [12][13][14], and 4) results in profound fear extinction learning deficits [13,14], even in the absence of an obesogenic phenotype [15].…”
Section: Introductionsupporting
confidence: 67%
“…Obesity is highly comorbid with anxiety and stress-related disorders. Our studies indicate that consumption of an obesogenic WD during adolescence heightens stress reactivity, promotes anxiety-like behaviors, and impairs the structural integrity of neural substrates implicated in stress-induced psychopathology in rats [12][13][14][15]. Furthermore, there is support to the notion that impairments in brain and behavior can occur even in the absence of an obesogenic phenotype [13,[57][58][59][60][61][62][63]].…”
Section: Obesogenic Diets Trigger Redox Dysregulation and Neuroinflammentioning
confidence: 59%
See 2 more Smart Citations
“…We would like to thank the staff at the animal care facility. This manuscript has been released as a preprint in bioRxiv ( Vega-Torres et al, 2020 ) as a significantly revised manuscript from another preprint listed in the same repository ( Vega-Torres et al, 2019 ).…”
mentioning
confidence: 99%